EFEKTIVITAS KEBIJAKAN KEPEMIMPINAN TERHADAP PRODUKTIVITAS MASYARAKAT (Riset pada Desa Majegan Kecamatan Tulung Kabupaten Klaten Periode Tahun 2016 – 2017) - Hendri Pamukas; Mulyanto Mulyanto (Universitas Slamet Riyadi, 2020)
This study aims to know, examine and analyze the influence of leadership, communication, commitment and compensation to the productivity of people with motivation and trust as intervening variables in the village Majegan Tulung District Klaten Period Year 2016 – 2017. The data analysis technique used is path analysis, which will be tested by t test, F test and R2 test, Correlations, direct influence and indirect influence and total influence. Data collection techniques using questionaires, researchers took a sample of 50 respondents. T test results show that leadership, commitment and compensation have a significant positive effect on motivation while communication has a negative and insignificant effect on motivation; communication, commitment and compensation have a significant positive effect on trust while leadership has a negative and insignificant effect on trust; leadership, communication, compensation, motivation and trust have a positive and significant effect on productivity while commitment has positive and insignificant effect on productivity. F test results show that leadership, communication, commitment, compensation, motivation and trust together positively and significantly affect the productivity of society. The result of determination coefficient test shows that the value of R square total is 0,987, meaning that productivity variable is explained by leadership, communication, commitment, compensation, motivation and trust equal to 98,7% and the rest equal to 1,3% explained other factor outside research model, variable satisfaction and organizational culture. The result of path analysis shows that the direct path of compensation to Productivity is the most dominant path to productivity directly, hence, to increase productivity directly more effectively the use of compensation variables.